Impact of physical activity on the level of development of the physical qualities of athletes 12–15 years old, involved in kettlebell lifting at the stage of initial training - Джим, Віктор; Канунова, Людмила (Slobozhanskyi Herald of Science and Sport, 2018)
Viktor Dzhym & Liudmyla Kanunova Purpose: to investigate the development of the physical qualities of athletes 12–15 years old, involved in kettlebell lifting, under the influence of practicing kettlebell lifting during the one-year macrocycle. Material & Methods: studies were conducted in Complex Youth Sports School No. 16 and Public Institution Complex Youth Sports School No. 8 of Kharkiv with athletes 12–15 years old engaged in kettlebell lifting during the one-year macrocycle in the amount of 30 people. The following research methods were used: analysis of literary sources and testing of the level of motor qualities in certain age categories. Results: pedagogical testing is presented to determine the level of motor capabilities of young athletes 12–15 years old engaged in kettlebell lifting. Exercises were identified that are advisable to use at these stages of preparation: running at 60 meters; at 1500 m; number of jumps in 30 seconds, standing long jump; flexion and extension of the arms in the support lying on the floor; raising legs hanging on the wall bars. Conclusion: as a result of the testing of motor skills using non-specific exercises for kettlebell lifting, it was found that the performance improves every year in all exercises (p>0,05), especially in 60 m running, which significantly increased in the age range from 13 to 14 years and in the race for 1500 m, from 14 to 15 years. The speed-strength abilities of young athletes aged 12–15 years who are involved in kettlebell lifting were more pronounced in the age range from 13 to 14 years.